Rapid and simultaneous determination of histidine metabolism intermediates in human and mouse microbiota and biomatrices. (10th July 2021) - Acuña, Inmaculada; Ruiz, Alicia; Cerdó, Tomás; Cantarero, Samuel; López‐Moreno, Ana; Aguilera, Margarita; Campoy, Cristina; Suárez, Antonio
Abstract: Histidine metabolism is a key pathway physiologically involved in satiety, recognition memory, skin, and neural protection and allergic diseases. Microbiologically‐produced imidazole propionate induces type II diabetes and interferes with glucose lowering drugs. Despite their determinant health implications, no single method simultaneously assesses histidine metabolites in urine, feces, and microbiota. The aim of this study was to develop a simple, rapid, and sensitive method for the determination of histidine and its major bioactive metabolites histamine, N‐acetylhistamine, imidazole‐4‐acetate, cis ‐urocanate, trans ‐urocanate, glutamate and imidazole propionate, using ultrahigh‐performance liquid chromatography with electrospray ionization tandem mass spectrometry. An innovative simple extraction method from small aliquots of human and mice urine, feces and microbial cell extracts was coupled to separation in a 6.5 min chromatographic run. The successful performance allowed accurate and precise quantification of all metabolites in mouse feces, suggesting broad exchange of histidine metabolites between the gut and mice. Higher urine histamine, histamine to histidine ratio, and imidazole‐4‐acetate pointed to an underlying inflammatory or allergic process in mice compared to human subjects. N‐acetylhistamine and imidazole propionate were detected in human and mouse feces, confirming its origin from gut microbial metabolism. Our novel and robust analytical method captured histidine metabolism in a single assay that will facilitate broad and deep histidine metabolic phenotyping assessing the impact of microbiota on host health in large‐scale human observational and interventional studies.